Comprehending thyroid cancer in Sri Lanka: current trends and outstanding questions - Sashiprabha Nawaratne; Saddharma Weerakoon; Janaki Vidanapathirana; Malawige Amila Suranga (College of Community Physicians of Sri Lanka, 2022)
Background and Objectives: In Sri Lanka, thyroid cancer (TC) is the second commonest cancer among females and third commonest cancer in both sexes. The aim of the study was to describe the trend of TC according to sex, age and histology type in Sri Lanka from 2005-2019. Methods: Study analysed secondary data from the National Cancer Registry Sri Lanka. Age standardized rates (ASR) of thyroid cancer were extracted for the respective years. Age group specific incidence rates were calculated for each year under consideration. Join Point software version 4.9.0.0 was used to analyse trends. Best fit models reported, by Annual Percentage Change and Average Annual Percentage Change, 95% CI. A p-value